2017
DOI: 10.1186/s12909-017-1065-2
|View full text |Cite
|
Sign up to set email alerts
|

A national stakeholder consensus study of challenges and priorities for clinical learning environments in postgraduate medical education

Abstract: BackgroundHigh quality clinical learning environments (CLE) are critical to postgraduate medical education (PGME). The understaffed and overcrowded environments in which many residents work present a significant challenge to learning. The purpose of this study was to develop a national expert group consensus amongst stakeholders in PGME to; (i) identify important barriers and facilitators of learning in CLEs and (ii) indicate priority areas for improvement. Our objective was to provide information to focus eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 55 publications
3
40
0
Order By: Relevance
“…A national stakeholder consensus document identified overcrowded clinical environments, understaffing and service pressures and clinical workload as barriers to learning in the CLE (Kilty et al 2017). Consistent with other studies, the domains identified as most challenging from an improvement perspective were the "organization and conditions of work" and "time to learn with senior doctors during patient care" (Kilty et al 2017). The Bawa-Garba case in the United Kingdom is a poignant example of this (Vaughan 2018).…”
Section: Current Challenges In the Learning Environmentmentioning
confidence: 70%
See 3 more Smart Citations
“…A national stakeholder consensus document identified overcrowded clinical environments, understaffing and service pressures and clinical workload as barriers to learning in the CLE (Kilty et al 2017). Consistent with other studies, the domains identified as most challenging from an improvement perspective were the "organization and conditions of work" and "time to learn with senior doctors during patient care" (Kilty et al 2017). The Bawa-Garba case in the United Kingdom is a poignant example of this (Vaughan 2018).…”
Section: Current Challenges In the Learning Environmentmentioning
confidence: 70%
“…The subject of the clinical learning environment (CLE) is at the forefront of discussions by educators, accreditors, educational organizations, and health care professionals and has long been a focus of research and improvement efforts in medical education. A suboptimal CLE has been associated with adverse patient care and learning outcomes (GMC 2016;Kilty et al 2017;Gruppen et al 2018;Macy Foundation 2018). The current climate of financially constrained and understaffed health systems has increased pressure and expectation of, and negative consequences for trainee well-being.…”
Section: The Clinical Learning Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A high standard of quality in the residency program is important to achieve well-qualified radiologists. In fact, there is an established relationship between clinical learning environment and patient safety (71). Furthermore, with the rapid technical development within the field of radiology it must be argued that continuous learning throughout the career is required.…”
Section: Pedagogical Aspectsmentioning
confidence: 99%